Total inflammation in early protocol kidney graft biopsies does not predict progression of fibrosis at one year post‐transplant. Issue 7 (18th May 2016) - Dörje, Christina; Reisæter, Anna Varberg; Dahle, Dag Olav; Mjøen, Geir; Midtvedt, Karsten; Holdaas, Hallvard; Flaa‐Johnsen, Linda; Syversveen, Trygve; Hartmann, Anders; Jenssen, Trond; Scott, Helge; Reinholt, Finn P.
Abstract: Introduction: There is an uncertainty whether total inflammation in early protocol kidney graft biopsies is associated with fibrosis progression. We investigated whether total inflammation, both in fibrotic and non‐fibrotic areas, at week 6 would predict fibrosis progression at one yr post‐transplant. Methods: We included 156 single adult ABO compatible kidney recipients with adequate week 6 and one yr transplant protocol biopsies (312 biopsies). Biopsies were scored according to the current Banff criteria. In addition, fibrosis and inflammation in fibrotic and non‐fibrotic areas were scored in a 10‐grade semi‐quantitative eyeballing system from 0% to 100%. Results: Fibrosis increased significantly from week 6 to one yr both by the 10‐grade scoring system from 0.69 ± 1.07 to 1.45 ± 1.86, (mean ± SD), p < 0.001 and by Banff interstitial fibrosis (ci) scoring 0.81 ± 0.65 to 1.13 ± 0.87, p < 0.001. The 10‐grade scoring system detected a larger proportion of fibrosis progressors than the Banff scoring 40.4% vs. 35.5%, p < 0.001. No significant positive association was found between inflammation at week 6 and progression of fibrosis in either of the scoring systems. Conclusions: Total inflammation in kidney transplant biopsies at week 6 did not predict progression of fibrosis at one yr post‐transplant.